“Moros y cristianos”. The triumph over Otherness in the celebrations for the canonization of St. Ferdinand in Seville Cathedral (1671) - Macartney, Hilary; González-Román, María del Carmen (My University, 2022)
This paper examines the exotic otherness of Early Modern imagery and emblematics in the celebrations of the canonization of King Ferdinand III of Castile held in the Cathedral of Seville in 1671. In the first part, I focus on how the language used to articulate the difference, hybridity and assimilation of the "Moors", "Turks" and the so-called "Moriscos" was overwhelmingly visual, as can be seen in pictorial representations, engravings, ephemeral architecture and, especially, in the "Moors and Christians festivals" in Spain since the late Middle Ages. I consider some examples to illustrate how the stereotype of the "Moor" is configured and how during the sixteenth and seventeenth centuries in most of the festivals of the Hispanic monarchy these stereotypes were present. In the second part, Hilary Macartney focuses on the celebrations for the canonization of Ferdinand III of Castile in Seville in 1671, and the lavishly illustrated book that accompanied them. She considers examples of the triumphalist imagery featured in the celebrations, alongside the acknowledged artistic importance of the ephemeral decorations and the printed record, and the challenges of (re)interpretation in light of modern attitudes and agendas.
Keywords: Imaginería; Otro (Filosofía); Escultura moderna; Fernando III Rey de Castilla, Santo; Canonización; Otherness; Festivals; Hybridization; Stereotype; Imagery